2014
DOI: 10.1016/j.ijheatmasstransfer.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects and energy cost of gliding arc discharge treatment on the inactivation of Escherichia coli in water

Abstract: The present study investigated the residual effect of gliding arc discharge (GAD) treatment on the inactivation of bacteria in a large volume of water (i.e., 20 L). Pure water and air were introduced to GAD separately, and then both the gas and water treated by plasma were sent to bacteria-containing water. Water contaminated by Escherichia coli (E. coli) was first treated by GAD for 10, 13 and 16, and 25 min and then stored for the next 4 h, during which time the E. coli concentration and pH were measured. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Nitrite (NO 2 -) and nitrate ions (NO 3 -) are produced and increased in water by plasma discharge treatment [18][19][20] . In addition, the concentration of components such as ozone (O 3 ), hydrogen peroxide (H 2 O 2 ), and hydroxide (OH) radicals also changes by water plasma discharge treatment [21][22][23][24] . O 3 and H 2 O 2 have bactericidal action in water [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrite (NO 2 -) and nitrate ions (NO 3 -) are produced and increased in water by plasma discharge treatment [18][19][20] . In addition, the concentration of components such as ozone (O 3 ), hydrogen peroxide (H 2 O 2 ), and hydroxide (OH) radicals also changes by water plasma discharge treatment [21][22][23][24] . O 3 and H 2 O 2 have bactericidal action in water [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed a dielectric barrier discharge (DBD) plasma, a type of atmospheric pressure plasma, in a N 2 =O 2 =H 2 O gas mixture and described the dissociation of N 2 , O 2 , and H 2 O molecules due to electron collision, the generation of radicals, the reaction between radicals and molecules, and their dissolution in liquid. Owing to many practical studies of plasma irradiation of biological cells and the use of plasma-activated medium, [19][20][21] it is now commonly understood that RONS are key species for treatment applications in plasma medicine. However, the reaction of plasma-generated active species with the cell and cell membrane is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of impedance, nozzle, "knife-edge" diverging electrodes between which high voltage is introduced, insulating cover and high-power supply and when electric field is approximately 3 kV mm -1 , the arc discharge generates. Hence, due to high velocity, the arc length increases (thermal plasma) and temperature of ionized gas decreases, becoming non-thermal plasma (Kim et al 2014). At atmospheric pressure, this technology is very well known for degradation of various organic components present in water (Tiya-Djowe et al 2015;Slamani et al 2018).…”
Section: Different Methods Of Cold Plasma Discharges Used In Wastewater Treatmentmentioning
confidence: 99%
“…It also works to decrease TOC and COD in treated wastewater by enhancing the biodegradability and eradication of different pathogens including bacteria, fungi, and viruses (Zeghioud et al 2020). Various studies have revealed the antimicrobial efficacy of cold plasma technology (Lunov et al 2016;Lu et al 2014;Kim et al 2014). Furthermore, it is also an emerging technique in the biomedical sector for treating wastewater and inactivating microbes (Patange et al 2018).…”
Section: Cold Plasma Technology Working Mechanismmentioning
confidence: 99%
See 1 more Smart Citation